THE DETERMINANTS OF THE VOLUME OF ELECTRONIC TRANSACTION IN INDONESIA - Hotimah Febriyanti, Marsa
This study aims to examine the effect of e-money infrastructure, inflation rate, and e-money providers on the electronic transactions volume carried out in Indonesia. The development of the technology have changed the transaction system become more fast and easy. In 2014, Bank Indonesia launched the National Non-Cash Movement program to support the non-cash payment in the transaction. Several previous study have mentioned several factors that can affect the volume of electronic transactions. However, the author highlights three faactors: e-money infrastructures, inflation rate, and the number of e-money providers. This research uses a quantitative method, using secondary data from 2013 to 2020 downloaded from Bank Indonesia Website. Data was analyzed by sing multiple linear regression using IBM SPSS Statistics software. Based on the analysis, shows that e-money infrastructure, inflation rate, and e-money providers have a significant influence on different alpha (5% and 10%). And the three variables have a simultaneous effect of 82%.